2019
DOI: 10.1111/pai.13035
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and managing allergic conjunctivitis in childhood: The allergist’s perspective

Abstract: Allergic conjunctivitis in childhood often poses problems of diagnosis and management for the allergist. We present the salient points concerning the diagnosis and treatment of ocular allergy emerging from a large cohort survey conducted jointly in the departments of ophthalmology and paediatric allergy in a French teaching hospital. Seasonal acute conjunctivitis is a common disorder and not overly difficult to diagnose and treat when associated with rhinitis leading to allergic rhinoconjunctivitis. An ophthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 35 publications
0
28
0
7
Order By: Relevance
“…en, in late-phase response, activated eosinophils result in the release of inflammatory cytokines including eosinophil cationic protein (ECP), eosinophil peroxidase, neutrophil toxic oxygen free radicals, proteases, and 2 lymphocytes, among others, some such as major basic proteins (MBP) and ECP are toxic to the corneal epithelium [44,45] (Figure 1).…”
Section: Classical Biological Mechanismsmentioning
confidence: 99%
“…en, in late-phase response, activated eosinophils result in the release of inflammatory cytokines including eosinophil cationic protein (ECP), eosinophil peroxidase, neutrophil toxic oxygen free radicals, proteases, and 2 lymphocytes, among others, some such as major basic proteins (MBP) and ECP are toxic to the corneal epithelium [44,45] (Figure 1).…”
Section: Classical Biological Mechanismsmentioning
confidence: 99%
“…Jean-Luc Fauquert, one of the very few experts having triple expertise in pediatrics, allergy, and ophthalmology, reviews diagnosis and management of the various presentation of allergic conjunctivitis and provides very practical advice which will undoubtedly update your clinical practice. 1 The second educational article is a rostrum addressing oral immunotherapy (OIT) for treatment of food allergy, a topic that has been extensively studied in the latest articles published in this journal. [2][3][4][5] In addition, a recent position statement of the European Academy (EAACI) has evaluated the scientific evidence behind OIT and concluded that "Overall, trials have found substantial benefit for patients undergoing OIT".…”
Section: Antibiotic Use Favors Early-life Allergies Intrauterine Blomentioning
confidence: 99%
“…Two educational articles begin this issue: the first addressing one of the most common clinical challenge practicing pediatric allergists are facing, allergic conjunctivitis. Jean‐Luc Fauquert, one of the very few experts having triple expertise in pediatrics, allergy, and ophthalmology, reviews diagnosis and management of the various presentation of allergic conjunctivitis and provides very practical advice which will undoubtedly update your clinical practice . The second educational article is a rostrum addressing oral immunotherapy (OIT) for treatment of food allergy, a topic that has been extensively studied in the latest articles published in this journal .…”
mentioning
confidence: 99%
“…Allergic conjunctivitis (AC) is one of the most common ocular disorders in clinical practice [ 1 ], with a 28% incidence in China [ 2 ], a nearly 25% incidence in children in Europe [ 3 ], and between 20% and 30% incidence in the United States [ 4 ]. The major symptoms of AC are itching, swelling, and tearing, and in some severe cases, photophobia and pain could develop due to the involvement of the cornea [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%